Identifying the Value Co-Creation Model and Upgrading Path of Manufacturing Enterprises from the Value Network Perspective - Li, Gang; Wu, Jiayi; Li, Ning (Sustainability, 2022)
The servitization of manufacturing enterprises has two main directions: production servitization and product servitization. The value co-creation model describes the transformation process of servitization of manufacturing enterprises; it is far more complex than that of service enterprises, and requires more in-depth research. This paper explores the value co-creation model and upgrading path based on the servitization of manufacturing enterprises, based on the idea that the value network supported by information technology has become a vital support for the servitization value co-creation of manufacturing enterprises. Referring to the degree of servitization of manufacturing enterprises and the degree of integration of complementary resources among value network members, we explore the value co-creation model between manufacturing enterprises and each network subject. We obtain four models: double-low model, servitization leading model, resource complementary leading model, and double-high model. We then clarify the characteristics, scope of application, advantages, and disadvantages of each model, and the means of value creation. We also apply the rough set method to empirically test the feasibility of the classification parameters of the value co-creation model and the accuracy of the classification rules, using Chinese listed and non-listed manufacturing enterprises as a sample. The findings provide a theoretical reference and practical guidance for manufacturing enterprises to achieve sustainable development and determine the upgrade path of the value co-creation model.